Expanding the Frontiers: Revolutionizing Quantitative Data Analysis in Social Sciences with AI - Andreev, Hristo; Pericleous, Katerina; Kosmas, Petros C. (My University, 2025)
This chapter aims to discuss and explore the idea of using conversational artificial intelligence (AI)’s data analysis capabilities as a new way of data analysis and interpretation, effectively substituting both statistical package software and programming for statistical analysis. It seeks to provide a comprehensive overview of how AI tools can transform the landscape of data analysis in social sciences, making advanced statistical techniques more accessible and user-friendly. The chapter delves into the practicalities of conversational AI and its applications in social science research by showing some practical examples. Moreover, it compares AI tools with traditional toolkits for statistical analysis in terms of efficiency, accuracy and ease of use. Furthermore, the chapter addresses the potential challenges and limitations of this approach, ensuring a balanced perspective while offering guidance on how social scientists can integrate AI tools into their research workflow, including tested examples that demonstrate the practical benefits and drawbacks of this technology.